Prevalence of pulmonary tuberculosis and associated factors among adults living with HIV/AIDS in Ethiopia, systematic review and meta-analysis - Amlaku Nigusie Yirsaw; Berihun Agegn Mengistie; Eyob Getachew; Gebrehiwot Berie Mekonnen; Adamu Ambachew Shibabaw; Alex Ayenew Chereka; Gemeda Wakgari Kitil; Wubet Tazeb Wondie; Gebeyehu Lakew (BMC Infectious Diseases)
Abstract Background Tuberculosis (TB), caused by Mycobacterium tuberculosis (MTB), remains a global health crisis, especially in sub-Saharan Africa, where high human immune virus (HIV) prevalence exacerbates the problem. The co-infection of TB and HIV creates a deadly combination, increasing susceptibility and complicating disease progression and treatment. Ethiopia, classified as a high-burden country, faces significant challenges despite efforts to reduce co-infection rates. The rise of multidrug-resistant TB further complicates diagnosis and management, highlighting the urgent need for intensified efforts to combat this dual epidemic. Methods Studies searched through the search engine of Cochrane Library, PubMed, Web of Science, Google Scholar. Data from included studies was extracted, organized in Excel, and then analyzed using STATA 17. The overall effect across all studies was calculated using a random-effect model. Potential publication bias and heterogeneity in the results between studies were assessed using Egger’s test, forest plot, and I² statistic, respectively. Results According to this systematic review and meta-analysis, the overall prevalence of pulmonary tuberculosis(PTB) among adults living with human immune virus /aquered immune deficieciency syndrome(HIV/AIDS) in Ethiopia was 15% (95% CI: 8-23%). Several factors were independently associated with pulmonary tuberculosis, including CD4 count below 200 cells/mm³ (OR = 4.491, 95% CI: 1.0001–8.132), WHO clinical stage III (OR = 4.487, 95% CI: 2.264–6.710)), WHO clinical stage IV (OR = 6.905, 95% CI: 5.239–8.571), smokers (AOR = 3.749, 95% CI: 2.626–5.271), ambulatory adults (AOR = 1.887, 95% CI: 1.439–2.335). Conclusion This systematic review and meta-analysis found a significant 15% pooled prevalence of pulmonary tuberculosis (PTB) among adults living with HIV/AIDS in Ethiopia. The prevalence was notably higher in individuals with lower CD4 counts, advanced HIV stages (III and IV), and in smokers. These findings underscore the need for early detection, targeted interventions, and integrated TB control programs with HIV care to mitigate the burden of PTB in this population.